Isoliquiritigenin Protects Against Pancreatic Injury and Intestinal Dysfunction After Severe Acute Pancreatitis via Nrf2 Signaling - Man Zhang; Yan-Qing Wu; Ling Xie; Jiang Wu; Ke Xu; Jian Xiao; Da-Qing Chen (Frontiers Media S.A., 2018)
Severe acute pancreatitis (SAP) is a digestive system disease that is associated with a range of complications including intestinal dysfunction. In this study, we determined that the chalcone compound, isoliquiritigenin (ISL), reduces pancreatic and intestinal injury in a mouse model of SAP. These effects were achieved by suppressing oxidative stress and the inflammatory responses to SAP. This was evidenced by a reduction in histological score, and malondialdehyde (MDA), interleukin (IL)-6, tumor necrosis factor (TNF)-α and cleaved-caspase-3 (c-caspase-3) protein along with an increase in Nrf2, hemeoxygenase-1 (HO-1), quinone oxidoreductase 1 (NQO1), and superoxide dismutase (SOD). We then used Nrf2-/- mice to test the protective effect of Nrf2 during ISL treatment of SAP. Our results indicated that Nrf2-/- mice had greater pancreatic injury and intestinal dysfunction than wild-type mice. They also had reduced adherens junctions (P120-catenin) and tight junctions (occludin), and increased activated nuclear factor-κB (NF-κB) protein. In Nrf2-/- mice, ISL was less effective at these functions than in the WT mice. In conclusion, this study demonstrated that ISL exerts its protective effects against oxidative stress and inflammatory injury after SAP via regulation of the Nrf2/NF-κB pathway. It also showed that the efficacy of ISL in repairing the intestinal barrier damage caused by SAP is closely related to the Nrf2 protein. Our findings demonstrated that Nrf2 is an important protective factor against SAP-induced injuries in the pancreas and intestines.